IMPLEMENTASI E-SERVICE UNTUK PELAYANAN PRIMA DENGAN METODE PIECES FRAMEWORK - Atik Budi Paryanti (STIKOM CKI, 2018)
To find out if the LHP Mobile app is running as it should, it is necessary to evaluate the performance of the app. Evaluations can be done in different ways and at different levels depending on the purpose of the evaluation. In conducting activities of analysis and evaluation of information systems there are several methods or models of analysis that can be used one of which is the analysis model PIECES Framework. To facilitate the evaluation, we offer an analytical approach with the PIECES framework outlining 6 focuses of weakness analysis: Performance, Information and Data, Economics, Control and Security, Efficiency and Service. The purpose of this study is to measure the level of satisfaction and importance, to know the strengths and weaknesses and to analyze what components need to be improved the quality of services contained in the LHP Mobile application. Primary data was obtained from the distribution of questionnaires to 16 LHP Mobile application users to obtain the level of importance and the level of user satisfaction.